A Predictive Preoperative and Postoperative Nomogram for Postoperative Potency Recovery after Robot-Assisted Radical Prostatectomy. Issue 4 (25th October 2021) - Bhat, K. R. Seetharam; Covas Moschovas, Marcio; Sandri, Marco; Dell'Oglio, Paolo; Onol, Fikret F.; Rogers, Travis; Reddy, Sunil; Noel, Jonathan; Roof, Shannon; Sighinolfi, Maria Chiara; Rocco, Bernardo; Patel, Vipul R.
Abstract : Purpose: Prediction of potency recovery following robot-assisted radical prostatectomy (RARP) is useful for better patient counseling and postoperative treatment strategies. In this study we propose a preoperative and postoperative nomogram to predict postoperative potency recovery following RARP. Materials and Methods: Patients from development set (6, 502) were selected to develop the nomograms, and patients in validation set (2, 706) were used for validation. Cox regression models were fitted on the development cohort to predict potency recovery after RARP using as prognostic factors the covariates selected. Two nomograms were drawn using the regression coefficients of the preoperative and postoperative Cox models. Results: The discrimination ability of the preoperative model was evaluated on the development cohort using the receiver operator curves estimated at 3, 6, 12 and 24 months. The AUC at these time points was 0.726, 0.734, 0.754, and 0.778, respectively. The areas under the curve of the postoperative model at 3, 6, 12 and 24 months were 0.746, 0.756 and 0.777, and 0.801, respectively. Preoperative and postoperative predictive models were validated using a separate set of 2, 706 patients. The AUCs of the preoperative model at 3, 6, 12 and 24 months were 0.789, 0.772, 0.768, and 0.778, respectively. The ROC curves of the postoperative model at 3, 6, 12 and 24 months with AUCs of 0.807, 0.797, 0.793 and 0.798, respectively. Along with age and preoperative sexual function, nerve-sparing technique determines the potency outcomes justifying better AUC for postoperative model vs the preoperative model. Conclusions: The above nomograms help us to predict with good accuracy the probability of potency recovery within 3, 6, 12 and 24 months following surgery taking into consideration preoperative and postoperative factors. This is a novel tool for the care giver to predict realistic expectation of potency outcomes to the patients, while preoperative and immediate postoperative counseling.